Comparative Assessment of the Risk of Unfavorable Outcome after Percutaneous Coronary Interventions in Patients with IHD with Concomitant Chronic Obstructive Pulmonary Disease, Possibilities of Drug Correction (International Journal of Psychosocial Rehabilitation, 2020)
Objective: to make a comparative assessment of the risk of unfavorable outcome after percutaneous coronary interventions in patients with coronary heart disease with concomitant chronic obstructive pulmonary disease to determine the possibilities of drug correction. Materials and methods: Results of PCI of 726 patients with IHD made the basis of the work: group I consisted of 106 patients who underwent PCI with COPD; group II included 620 patients after PCI without COPD. Results: The presence of concomitant COPD is associated with an increased risk of hospital mortality and the development of cardiovascular complications (CVC) during the observation period after PCI. Thus, patients with COPD were statistically significantly older, female prevailed, and a more severe course was determined (Killip III, in 15.1% versus 4.1% in group II; p